1994
DOI: 10.1006/cbir.1994.1050
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretion of latent elastase activity following contact between human skin fibroblasts and elastin derived peptides.

Abstract: Elastin-derived peptides were previously shown to influence human skin fibroblasts (HSF) chemotaxis and proliferation (Ghuysen et al., 1992). We report here that culturing HSF on kappa-elastin (kappa E) but not onto fibronectin (FN) enhanced the secretion of latent elastinolytic activity. The proteinase involved was identified as the 72 kDa gelatinase A. Moreover, HSF-kappa E as well as HSF-FN interactions modulated the secretions of Il1 induced expressions of elastinolytic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Hinek et al potentially providing a longer-lasting rejuvenation of the aging skin. We have demonstrated that digestion of bovine neck ligament elastin with Proteinase K produces a mixture of numerous heterogenic peptides of lower molecular weight than Kappa-Elastin and other chemical digests of insoluble elastin that have been previously described as inducers of diverse biological effects in cultures of several cell types, including fibroblasts [36,[40][41][42][43][44][45][46][47][48]. Presented results indicate that our novel preparation, in addition to a modest (up to 30%) net increase in cellular proliferation, tremendously enhances synthesis and deposition of both major components of elastic fibers, elastin and microfibrillar proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hinek et al potentially providing a longer-lasting rejuvenation of the aging skin. We have demonstrated that digestion of bovine neck ligament elastin with Proteinase K produces a mixture of numerous heterogenic peptides of lower molecular weight than Kappa-Elastin and other chemical digests of insoluble elastin that have been previously described as inducers of diverse biological effects in cultures of several cell types, including fibroblasts [36,[40][41][42][43][44][45][46][47][48]. Presented results indicate that our novel preparation, in addition to a modest (up to 30%) net increase in cellular proliferation, tremendously enhances synthesis and deposition of both major components of elastic fibers, elastin and microfibrillar proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the endogenous serine elastase is similar to other elastases, such as neutrophil or pancreatic elastase, it could activate latent MMPs (12) and degrade TIMPs, and, by destabilizing TIMP-MMP complexes, facilitate release of the active enzyme (13). Elastases also release elastin or FN-derived peptides as well as ECM-incorporated FGF-2 (10), all of which can increase MMP expression and activity (14,15,32). Whereas elastases do not require proteolysis for activation, MMP-mediated 30 The (30), may enhance vascular elastolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported that elastin affects the proliferation [47,48], differentiation [49], migration [50,51], and anti-apoptosis of cells [32]. On the other hand, it is known that the SELP modifies the proliferation [52] and differentiation of cells [19].…”
Section: Discussionmentioning
confidence: 99%